2011
DOI: 10.1007/978-3-7091-0794-2_2
|View full text |Cite
|
Sign up to set email alerts
|

Sparsity Optimized High Order Finite Element Functions on Simplices

Abstract: This paper deals with conforming high-order finite element discretizations of the vectorvalued function space H(div) in 2 and 3 dimensions. A new set of hierarchic basis functions on simplices with the following two main properties is introduced. Provided an affine simplicial triangulation, first, the divergence of the basis functions is L2-orthogonal, and secondly, the L2-inner product of the interior basis functions is sparse with respect to the polynomial order p. The construction relies on a tensor-product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 50 publications
2
10
0
Order By: Relevance
“…For the triangle and tetrahedron, our construction is based on the concept of scaled polynomials as described by Karniadakis and Sherwin (1999), Schöberl and Zaglmayr (2005), Zaglmayr (2006) and the subsequent work of Beuchler et al (2012a). See also Beuchler and Schöberl (2006); Beuchler and Pillwein (2007); Beuchler et al (2012b) and Beuchler et al (2013) for more details on obtaining good sparsity properties via appropriate selection of Jacobi polynomials.…”
Section: Previous Workmentioning
confidence: 99%
“…For the triangle and tetrahedron, our construction is based on the concept of scaled polynomials as described by Karniadakis and Sherwin (1999), Schöberl and Zaglmayr (2005), Zaglmayr (2006) and the subsequent work of Beuchler et al (2012a). See also Beuchler and Schöberl (2006); Beuchler and Pillwein (2007); Beuchler et al (2012b) and Beuchler et al (2013) for more details on obtaining good sparsity properties via appropriate selection of Jacobi polynomials.…”
Section: Previous Workmentioning
confidence: 99%
“…Warburton et al [12] observed that the stiffness matrix for C 0 basis functions defined using Jacobi polynomials with a specific choice of parameters yielded very sparse and banded blocks in the discretization of the Laplacian. Similarly, Beuchler et al [13,14] proposed using integrated Jacobi polynomials to construct topological basis functions that yield sparse and nearly diagonal stiffness matrices on simplicial meshes. These bases rely on orthogonality properties to sparsify global discretization matrices; in contrast, we leverage properties of Bernstein-Bezier basis functions to simultaneously sparsify elemental derivative operators and factorize elemental lift operators to enable GPU friendly implementations.The paper is structured as follows -we review the formulation of DG methods for the first order wave equation in Section 2.…”
mentioning
confidence: 99%
“…We refer to [6] for generalizations to the three dimensional case and to [9] for other PDE's like the Maxwell equations. Similar recursion formulas to the shown formula can be found for the interior block of the mass matrix as well.…”
Section: Discussionmentioning
confidence: 99%